Fractional Maximal Effect Method for In Vitro Synergy between Amoxicillin and Ceftriaxone and between Vancomycin and Ceftriaxone against Enterococcus faecalis and Penicillin-Resistant Streptococcus pneumoniae - Desbiolles, Norbert (American Society for Microbiology, 2001)
In the present study we assessed the use of a new in vitro testing method and graphical representation of the results to investigate the potential effectiveness of combinations of amoxicillin (AMZ) plus ceftriaxone (CRO) and of CRO plus vancomycin (VAN) against strains of Streptococcus pneumoniae highly resistant to penicillin and cephalosporins (PRP strains). We used the fractional maximal effect (FME) method of time-kill curves to calculate adequate concentrations of the drugs to be tested rather than relying on arbitrary choices. The concentrations obtained, each of which corresponded to a fraction of the maximal effect, were tested alone and in combination with the bacterial strains in a broth medium. Synergy was defined as a ratio of observed effect/theoretical effect, called FME, of greater than 1, additivity was defined as an FME equal to 1, and antagonism was defined as an observed effect lower than the best effect of one of the antibiotics used alone. The area between antagonism and additivity is the indifference zone. The well-known synergy between amoxicillin and gentamicin against a reference strain of Enterococcus faecalis was confirmed, with a best FME equal to 1.07. Two strains of PRP, strains PRP-1 and PRP-2, were studied. The MICs for PRP-1 and PRP-2 were as follows: penicillin, 4 and 16 μg/ml, respectively; AMZ, 2 and 8 μg/ml, respectively, CRO, 1 and 4 μg/ml, respectively; and VAN, 0.5 and 0.25 μg/ml, respectively. For PRP-1 the best FME for the combination AMZ-CRO was 1.22 with drug concentrations of 1.68 mg/liter for AMZ and 0.17 mg/liter for CRO; the best FME for the combination VAN-CRO was 1.75 with VAN at 0.57 mg/liter and CRO at 0.17 mg/liter. For PRP-2 the best FME obtained for the combination AMZ-CRO was 1.05 with drug concentrations of 11.28 mg/liter for AMZ and 0.64 mg/liter for CRO; the best FME obtained for the combination VAN-CRO was 1.35 with VAN at 0.25 mg/liter and CRO at 1.49 mg/liter. These results demonstrated the synergy of both combinations, AMZ-CRO and VAN-CRO, against PRP strains at drug concentrations achievable in humans. Consequently, either of the combinations can be proposed for use for the treatment of PRP infections.